RESEARCH ON THE FORMATION OF URBAN RESIDENTIAL LIFESTYLES THROUGH CASE STUDIES OF LOWLAND CITY SAGA AND NON－LOWLAND CITY KITAKYUSYU - J. Ge; K. Hokao (International Association of Lowland Technology, 2005)
In this paper, we firstly put forward the conception of residential lifestyles; and suitably questionnaire surveys were conducted in two cities of Japan- lowland city Saga and non-lowland city Kitakyusyu. Through the analysis of the questionnaire data, we got hold of the characteristics of residential preference patterns, residential emphasis on dwelling selection, as well as the evaluation on residential environment satisfaction. Furthermore, the comparison between the two cities helped to make clear the similarity and difference of the residential emphasis between lowland city and non-lowland city. The results of the research will not only be benefit to the understanding of the diversification of residential lifestyles, but also provide more information to the planning and developing of residential environment effectively and efficiently by understanding the residential preference, emphasis and demands of various patterns.